Information technology. International standardized profiles TB, TC, TD and TE. Connection-mode transport service over connection-mode network service. Definition of profile TC51, provision of the OSI connection-mode transport service using the OSI connection-mode network service in an end system attached to a CSMA/CD LAN Part 12, (15th July 1995) - British Standards Institution,
No abstract available